2015
DOI: 10.1002/2015wr017325
|View full text |Cite
|
Sign up to set email alerts
|

The atmospheric transport of iodine‐129 from Fukushima to British Columbia, Canada and its deposition and transport into groundwater

Abstract: The Fukushima-Daiichi nuclear accident (FDNA) released iodine-129 (15.7 million year half-life)and other fission product radionuclides into the environment in the spring and summer of 2011. 129 I is recognized as a useful tracer for the short-lived radiohazard 131 I, which has a mobile geochemical behavior with potential to contaminate water resources. To trace 129 I released by the FDNA reaching Canada, preaccident and post-accident rain samples collected in Vancouver, on Saturna Island and from the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Approximately 76 % of the shallow groundwater locations (16 of 19 sites) exceeded the maximum allowable concentration (MAC) of 10 mg N L −1 in the Canadian Drinking Water Guidelines (Health Canada, 2013). These nitrate exceedances were consistent with previous observations of high nitrate concentrations in shallow wells in the aquifer (Hii et al, 1999). Previous studies reported NO − 3 concentrations exceeding the MAC in 58 %, 69 %, and 59 % of wells (Wassenaar, 1995;Zebarth et al, 1998;Wassenaar et al, 2006), respectively.…”
Section: Groundwater Nitrate Concentrationssupporting
confidence: 92%
“…Approximately 76 % of the shallow groundwater locations (16 of 19 sites) exceeded the maximum allowable concentration (MAC) of 10 mg N L −1 in the Canadian Drinking Water Guidelines (Health Canada, 2013). These nitrate exceedances were consistent with previous observations of high nitrate concentrations in shallow wells in the aquifer (Hii et al, 1999). Previous studies reported NO − 3 concentrations exceeding the MAC in 58 %, 69 %, and 59 % of wells (Wassenaar, 1995;Zebarth et al, 1998;Wassenaar et al, 2006), respectively.…”
Section: Groundwater Nitrate Concentrationssupporting
confidence: 92%
“…Iodine-129 is a major environmental pollutant [11]. Its continued use since 1940 has caused a dangerous increase of this isotope in the environment, with a greater accumulation in surface and groundwater [12,13].…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%
“…I distribution and dispersion in the troposphere • The source of the deposited 129 I in glacier snowpack is located in the upper troposphere • A hypothetic model on the transport, dispersion, and removal of 129 I in the troposphere is provided particulates during transport, which have large residence time and can be dispersed over large distances Keogh et al, 2009;Masson et al, 2011;Reithmeier et al, 2006). However, 129 I released into the lower troposphere has a much smaller residence time of about two weeks, as demonstrated by the increased concentrations of 129 I found in the Northeast British Columbia of Canada (Herod et al, 2015). However, 129 I released into the lower troposphere has a much smaller residence time of about two weeks, as demonstrated by the increased concentrations of 129 I found in the Northeast British Columbia of Canada (Herod et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Fukushima accident, since violent explosions occurred at very high temperatures (more than 1400°C), radioisotopes were first expelled and dispersed to the atmosphere. However, 129 I released into the lower troposphere has a much smaller residence time of about two weeks, as demonstrated by the increased concentrations of 129 I found in the Northeast British Columbia of Canada (Herod et al, 2015). For the radioisotope fraction injected into the stratosphere the transit time back to the troposphere is of the order of years and the transport at this high altitude contributes to the 129 I dispersion over the globe (Blinov et al, 2000), and probably to the remote alpine glaciers in the Tibetan Plateau, as the data presented later in this study show.…”
Section: Introductionmentioning
confidence: 99%